Micro-CT evaluation of marginal and internal fit of cemented polymer infiltrated ceramic network material crowns manufactured after conventional and digital impressions. Issue 1 (January 2019) - Dauti, Rinet; Cvikl, Barbara; Lilaj, Bledar; Heimel, Patrick; Moritz, Andreas; Schedle, Andreas
Abstract: Purpose: Purpose of this study was to evaluate the accuracy of fit of cemented polymer infiltrated ceramic network (PICN) material crowns manufactured after digital and conventional impression techniques using micro computed tomography (CT). Furthermore to determine the cement space volume and porosities in the cement layer. Methods: A molar typodont tooth was prepared for PICN material crowns and replicated thirty times. The dies were randomly divided into three groups of 10 specimens each according to the impression technique: 3M True Definition Scanner (TDS), cara TRIOS (Trios) and Impregum Penta Soft (Impregum). PICN material crowns were milled for each specimen from Vita Enamic blocks and cemented on their respective dies. The absolute marginal discrepancy (AMD), internal fit (IG), total cement space volume (TVC) and marginal porosities (VP) were measured using Micro-CT. Results: Mean and standard deviations values in μm for the AMD were: TDS 140.1 (28.4); Trios 253.7 (56.8); Impregum 220.2 (101.1). IG values in μm: TDS 173.1 (27.7); Trios 222.2 (22.4); Impregum 211.6 (55.9). TVC in mm 3 : TDS 19.82 (2.9); Trios 23.67 (2.01); Impregum 23.77 (5.09). VP in mm 3 : TDS 0.38 (0.09); Trios 0.36 (0.10); Impregum 0.51 (0.31). Conclusions: TDS group showed significantly better marginal and internal fit than the Trios group. No difference of the parameters was detected between the Impregum and both digital groups which implies that the digital impression technique is suitable in the manufacturing process of PICN material crowns.